The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s11356-017-0709-4
|View full text |Cite
|
Sign up to set email alerts
|

Polybrominated diphenyl ethers (PBDEs) and hydroxylated PBDEs in human serum from Shanghai, China: a study on their presence and correlations

Abstract: Polybrominated diphenyl ethers (PBDEs) are becoming a public health concern because of their potential toxicity, from endocrine disruption system to neurodevelopmental impairments. Nonetheless, information on their levels in human blood is scarce. In this study, human serum samples collected in Shanghai, China, were analyzed for the concentrations of PBDEs and their hydroxylated metabolites (OH-PBDEs). Eight PBDE congeners and six OH-PBDE congeners were quantified in serum samples by gas chromatography with ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Similar results were observed in serum among a sample of 137 pregnant women in NC, where BDE47 was strongly correlated to BDE99 (r = 0.80) and BDE100 (r = 0.80), yet weaker for BDE153 (r = 0.52) (Stapleton et al, 2011). However, among a serum sample of men and women in Shanghai, China (n = 25), BDE47 was strongly correlated to both BDE100 (r = 0.97) and BDE154 (r = 0.97) (Xu et al, 2018). They also observed a strong correlation between BDE100 and BDE154 (r = 0.99).…”
Section: Discussionmentioning
confidence: 91%
“…Similar results were observed in serum among a sample of 137 pregnant women in NC, where BDE47 was strongly correlated to BDE99 (r = 0.80) and BDE100 (r = 0.80), yet weaker for BDE153 (r = 0.52) (Stapleton et al, 2011). However, among a serum sample of men and women in Shanghai, China (n = 25), BDE47 was strongly correlated to both BDE100 (r = 0.97) and BDE154 (r = 0.97) (Xu et al, 2018). They also observed a strong correlation between BDE100 and BDE154 (r = 0.99).…”
Section: Discussionmentioning
confidence: 91%
“…The levels of cord serum PBDEs in our study (23.17 ng/g lipid) were generally lower than those reported in North America (33.32 ng/g lipid in the USA and 93.66 ng/g lipid in Canada) (Chen et al, 2013;Foster et al, 2011). However, they were ve orders of magnitude higher than those reported in serum samples collected during other studies performed on general populations in various areas of China, such as Hong Kong (4.45 ng/g lw; Ho et al, 2015) and Shanghai (2.16 ng/g lw; Xu et al, 2018). The possible reason for the high PBDEs levels in our study might be associated with high amounts of exposure in our study area (Li et al, 2017), which is located near several large-scale BFR production factories.…”
Section: Discussionmentioning
confidence: 57%
“…Levels for BDE47 in the U.S. population are roughly 3 to 10 times higher than levels in populations from different studies conducted in European countries (Sjodin et al, 2018). A study conducted in China in 2017 quantified BDEs and OH-BDEs in human serum and their findings showed that BDE47 and 6-OH-BDE47 were the congeners present at highest concentrations in the samples studied (Xu et al, 2018).…”
Section: Introductionmentioning
confidence: 71%